2005
DOI: 10.1029/2005gl024191
|View full text |Cite
|
Sign up to set email alerts
|

Targeted 3‐D prestack depth imaging at Legs 190‐196 ODP drill sites (Nankai Trough, Japan)

Abstract: [1] Target-oriented 3-D prestack depth migration (PSDM), tied to known depths of key reflections at three ODP drill sites in the Nankai Trough, provides an improved representation of the subsurface depths and P-wave velocities around the drill holes. The resulting velocity volume is representative of the ''in situ'' velocities and allows us to extend the 1-D logging and core velocity data from the drill sites to the entire seismic transect. The PSDM velocity gradients closely match those at the drill sites, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 18 publications
2
31
1
Order By: Relevance
“…For several margins, it has been suggested that at the onset of subduction, the décollement preferentially localizes in weak strata (e.g., Moore, 1989;Deng and Underwood, 2001;Kopf and Brown, 2003). This is inferred from mechanical data, and often corroborated by seismic reflection data in which the plate boundary proto-décol-lement can be correlated with negative-polarity reflectors in the incoming sequence (e.g., MacKay, 1995;Moore et al, 1995Moore et al, , 1998Costa Pisani et al, 2005).…”
Section: Introductionmentioning
confidence: 67%
“…For several margins, it has been suggested that at the onset of subduction, the décollement preferentially localizes in weak strata (e.g., Moore, 1989;Deng and Underwood, 2001;Kopf and Brown, 2003). This is inferred from mechanical data, and often corroborated by seismic reflection data in which the plate boundary proto-décol-lement can be correlated with negative-polarity reflectors in the incoming sequence (e.g., MacKay, 1995;Moore et al, 1995Moore et al, , 1998Costa Pisani et al, 2005).…”
Section: Introductionmentioning
confidence: 67%
“…Because of the great water depths (>6,000 m), the water velocity (which does not vary greatly) has a large effect on the migrations. We estimate that within the sediment section, which is less than 1,000-mthick, our velocity errors are no more than approximately 200 to 400 m s −1 based on PSDM sediment velocity sensitivity in the high-resolution lines (e.g., Tsuru et al 2000;Costa Pisani et al 2005). Such velocity errors would result in a maximum of approximately 5% to 10% error in depth that would not affect our structural interpretations.…”
Section: Methodsmentioning
confidence: 91%
“…About 200 km north of the Muroto Transect, NanTroSEIZE established 13 drilling sites along the Kumano Transect off the Kii Peninsula where the plate boundary fault system is within reach of the Chikyu's riser drilling technology. In the course of numerous seismic and bathymetric surveys, the structure of the Nankai Trough off Shikoku was imaged extensively (e.g., Aoki et al, 1982;Ashi and Taira, 1992;Costa Pisani et al, 2005;Kodaira et al, 2000;Le Pichon et al, 1987;Moore et al, 1990Moore et al, , 1991Okino and Kato, 1995;Park et al, 1999Park et al, , 2000Stoffa et al, 1992;Taira and Ashi, 1993). A large volume of 3-D seismic reflection data was acquired in 1999 (R/V Ewing Cruise 9907/8) in an effort to image the décollement from the trench into the seismogenic zone (e.g., Bangs et al, 1999Bangs et al, , 2004Bangs and Gulick, 2005;Gulick et al, 2004).…”
Section: Geological Settingmentioning
confidence: 99%